2008
DOI: 10.1002/cncr.23590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of computed tomography screening for lung cancer on participants in a randomized controlled trial (NELSON trial)

Abstract: BACKGROUND. Computed tomography (CT) screening is an important new tool for the early detection of lung cancer. In the current study, the authors assessed the discomfort associated with CT scanning and the subsequent wait for results and health‐related quality of life (HRQoL) over time. METHODS. A total of 351 participants in the Dutch‐Belgian randomized controlled trial for lung cancer screening in high‐risk subjects (the NELSON trial) who had an appointment for a baseline CT scan were asked to complete quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 30 publications
2
82
1
7
Order By: Relevance
“…The first reported increased lung cancer-specific anxiety in those found to have an indeterminate lung nodule (15). In the second, participants were reported to have discomfort related to having to wait for the results of the CT scan and dreading those results (16). Our results support those of the NELSON trial.…”
Section: Original Researchsupporting
confidence: 77%
“…The first reported increased lung cancer-specific anxiety in those found to have an indeterminate lung nodule (15). In the second, participants were reported to have discomfort related to having to wait for the results of the CT scan and dreading those results (16). Our results support those of the NELSON trial.…”
Section: Original Researchsupporting
confidence: 77%
“…Few studies have examined the HRQoL effects of lung cancer screening with computed tomography (CT) [2][3][4][5]. Subjects receiving an indeterminate or positive result for a baseline CT screening have reported increased anxiety or fear of cancer [2] and more lung cancerspecific distress than subjects with a negative result [3].…”
mentioning
confidence: 99%
“…Subjects receiving an indeterminate or positive result for a baseline CT screening have reported increased anxiety or fear of cancer [2] and more lung cancerspecific distress than subjects with a negative result [3]. At short-term follow-up, when all subjects had negative CT results, these unfavourable effects on HRQoL were shown to have decreased and the differences between subjects with initially negative or positive/indeterminate results were no longer observed [2,4,5]. CT scanning caused only a little discomfort and had no major impact on HRQoL [4].…”
mentioning
confidence: 99%
“…The limited studies to date confirmed that those screened experience psychological distress while waiting for screening test results [25] and found that individuals with abnormal results perceived an increased risk of lung cancer and increased anxiety that diminished over time [26]. These findings suggest that patient education regarding the actual risk of lung cancer, known false positive rates, and expected benefits may help mitigate adverse psychological effects.…”
Section: Ethical Considerationsmentioning
confidence: 85%